2020
DOI: 10.1186/s12964-020-0528-y
|View full text |Cite
|
Sign up to set email alerts
|

The eEF2 kinase-induced STAT3 inactivation inhibits lung cancer cell proliferation by phosphorylation of PKM2

Abstract: Background: Eukaryotic elongation factor-2 kinase (eEF2K) is a Ca 2+ /calmodulin (CaM)-dependent protein kinase that inhibits protein synthesis. However, the role of eEF2K in cancer development was reported paradoxically and remains to be elucidated. Methods: Herein, A549 cells with eEF2K depletion or overexpression by stably transfected lentivirus plasmids were used in vitro and in vivo study. MTT and colony assays were used to detect cell proliferation and growth. Extracellular glucose and lactate concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
1
34
1
Order By: Relevance
“…This is in line with the fact that the role of eEF2K in cancer development is complex as revealed by apparently conflicting reports, which suggest eEF2K may promote or impair tumour growth or survival. For example, we recently reported that depletion of eEF2K promotes growth of A549 xenografts in mice [37]. In direct contrast, eEF2K is also highly expressed in other cancers (see, e.g., [38,39] and is also activated under conditions (such as nutrient depletion or hypoxia [8]) which occur within solid tumours; this will permit the enhanced expression of PD-L1 increasing the resistance of the tumour cells to immune attack.…”
Section: Gene Expression Profiles Of Eef2k and Cd274 (Pd-l1) In A Datmentioning
confidence: 99%
“…This is in line with the fact that the role of eEF2K in cancer development is complex as revealed by apparently conflicting reports, which suggest eEF2K may promote or impair tumour growth or survival. For example, we recently reported that depletion of eEF2K promotes growth of A549 xenografts in mice [37]. In direct contrast, eEF2K is also highly expressed in other cancers (see, e.g., [38,39] and is also activated under conditions (such as nutrient depletion or hypoxia [8]) which occur within solid tumours; this will permit the enhanced expression of PD-L1 increasing the resistance of the tumour cells to immune attack.…”
Section: Gene Expression Profiles Of Eef2k and Cd274 (Pd-l1) In A Datmentioning
confidence: 99%
“…The M2 isoform of pyruvate kinase (PKM2) (also named PKM, PK3, THBP1), an essential enzyme involved in glycolysis, is known to mediate the conversion of glucose to lactate in cancer cells under normoxic conditions [ 27 , 28 ]. Jing Li reported that phosphorylation of PKM2 and inactivation of STAT3 inhibited lung cancer cell proliferation [ 29 ]. Inhibitors of PKM2 could moderately decelerate tumor cell proliferation [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PKM2 is a speci c isoform of pyruvate kinase and a rate-limiting enzyme controlling the glycolysis process. The PKM2 is highly expressed in many types of tumors, including ovarian cancer [39][40][41][42][43]. Studies have shown that PKM2 can translocate to the nucleus, where it forms a complex with HIF-1α and acts as a transcription coactivator of HIF-1α to promote the transcription of HIF-1α targeted genes (such as glycolytic rate-limiting enzymes).…”
Section: Discussionmentioning
confidence: 99%